2017
DOI: 10.18632/oncotarget.20563
|View full text |Cite
|
Sign up to set email alerts
|

Activation-induced cytidine deaminase prevents pro-B cell acute lymphoblastic leukemia by functioning as a negative regulator in Rag1 deficient pro-B cells

Abstract: Activation-induced cytidine deaminase (AID) is essential for somatic hypermutation and class switch recombination in mature B-cells, while AID was also shown to play a role in developing pre-BCR/BCR-positive B-cells of the bone marrow. To further elucidate a potential function of Aid in the bone marrow prior to V(D)J-recombination, we utilized an in vivo model which exerts a B-cell developmental arrest at the pro-B cell stage with low frequencies of pro-B cell acute lymphoblastic leukemia (pro-B ALL) developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Leukemia caused by PU.1/Spi-B deletion strongly resembles fraction C large pre-B cells (Batista et al, 2018; Sokalski et al, 2011). We speculate that if driver mutations are induced by dysregulated AID in fraction B, such mutations would be positively selected by proliferation in fraction C. In support of this possibility, AID has been shown to be expressed in human and mouse pro-B cells (Auer et al, 2017; Cantaert et al, 2015). These results suggest that PU.1 is involved in the constraint of Aicda transcription in pro-B cells.…”
Section: Discussionmentioning
confidence: 79%
“…Leukemia caused by PU.1/Spi-B deletion strongly resembles fraction C large pre-B cells (Batista et al, 2018; Sokalski et al, 2011). We speculate that if driver mutations are induced by dysregulated AID in fraction B, such mutations would be positively selected by proliferation in fraction C. In support of this possibility, AID has been shown to be expressed in human and mouse pro-B cells (Auer et al, 2017; Cantaert et al, 2015). These results suggest that PU.1 is involved in the constraint of Aicda transcription in pro-B cells.…”
Section: Discussionmentioning
confidence: 79%
“…In particular, our analysis focused on R653H, V670A, and T844M mutations in Jak3 . Jak3 R653H and V670A mutations were recently observed in B-ALL generated in activation-induced cytidine deaminase (AID) deficient mice 49 . Human equivalents of Jak3 R653H and V670A have been described in human ALL (R657Q, V674F), and furthermore have been shown to function by activation of proliferation in response to interleukin-7 50 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that DNM2 plays a major role in the internalization of IL7R, TCR, and Notch ligand Delta like 1 (DIl-1), thereby triggering the development of ALL [110]. Recently, somatic mutations of DNM2 were identified in pro-B ALL, with all of the mutant variants centric to the middle domain [111]. Loss of functional mutations in DNM2 has resulted in the increase of IL7R cell surface expression in a Lmo2 transgenic T-ALL mouse model [112].…”
Section: Dynamin 2 (Dnm2)mentioning
confidence: 99%